Effect of Custom-Made Foot Orthotics on Multi-Segment Foot Kinematics and Kinetics in Individuals with Structural Hallux Limitus. - Martínez-Rico, Magdalena; Gijón-Noguerón, Gabriel; Ortega-Ávila, Ana Belén; Roche-Seruendo, Luis Enrique; Climent-Pedrosa, Ana; Sanchis-Sales, Enrique; Deschamps, Kevin (MDPI, 2024)
The first metatarsophalangeal joint (MTPJ) and the first ray are crucial in walking, particularly during propulsion. Limitation in this joint’s sagittal plane motion, known as hallux limitus, can cause compensatory movements in other joints. Some studies assessed the impact of various foot orthoses designs on the foot biomechanics; however, a comprehensive understanding is lacking. This study compared the effects of two custom-made foot orthoses (CFOs) on the foot joint kinematics and kinetics in patients with structural hallux limitus (SHL). In this quasi-experimental study, 24 patients with hallux limitus were assessed in three conditions: (i) barefoot, (ii) shod with a cut-out custom foot orthosis (cut-out CFO), and (iii) shod with an anterior forefoot-stabilized element custom foot orthosis (AFSE CFO), fitted into a minimalist neoprene shoe. Multi-segment foot kinematics and kinetics were assessed during the stance phase of the gait. A decrease in ankle and midfoot inversion, as well as in ankle plantarflexion, was found in both orthotic conditions. Regarding the first MTPJ, a greater dorsiflexion was observed with the patient being barefoot compared to both of the conditions under study. From the current finding, it should be concluded that neither of the custom foot orthoses produced the predefined functional effects.
Keywords: Cinemática; Pies - Enfermedades - Tratamiento; Foot orthosis; Structural hallux limitus; Kinematics; Kinetics